Extraarticular Manifestations of Rheumatoid Arthritis in a Multiethnic Cohort of Predominantly Hispanic and Asian Patients - Richman, Nicole C. (Wolters Kluwer Health, 2013)
We conducted a study to determine the prevalence of extraarticular manifestations (ExRA) in a cohort of predominantly Hispanic and Asian patients with rheumatoid arthritis (RA), to identify factors associated with the development of ExRA, and to compare the prevalence of ExRA between Hispanic and Asian patients. Patients with RA followed in the outpatient rheumatology clinics of a public hospital were included if they were aged ≥18 years and met the 1987 American College of Rheumatology criteria for the diagnosis of RA. We performed a cross-sectional analysis in which patients with ExRA were identified based on predefined criteria. We compared sociodemographic and clinical characteristics in patients with and without ExRA. Multivariate logistic regression was used to examine the association between sociodemographic variables, clinical characteristics, and the presence of ExRA. The prevalence of ExRA was 21.5%, and the most common manifestations were subcutaneous nodules (17.2%) and interstitial lung disease (3.6%). Hispanic patients were significantly more likely to develop ExRA than Asian patients (odds ratio, 2.53; 95% confidence interval, 1.26–5.09). The development of ExRA was also associated with disease duration, male sex, and seropositivity for serum rheumatoid factor.